Sustainable Schoolyards as Learning Landscapes - Beste Sabır Onat; Funda Yirmibeşoğlu (Iconarp International Journal of Architecture and Planning, 2022)
Learning for sustainability encourages informal learning, embeds daily usages and observations into the learning process, and has the potential to cultivate ecological-based habits for a sustainable future. We cannot separate the learning process and everyday life from each other. Therefore, the present research focuses on sustainable learning programs and designs in schoolyards within the framework of “learning landscapes,” which is an emerging topic that requires interdisciplinary approaches. This article aims to combine curriculum design, spatial design, informal learning, and ecological design themes and explain the practice-based processes in “Design Your Schoolyard” workshops. This participatory and hands-on project involves multiple stakeholders and unfolds this multilayered structure within its process. Nature-child connections are insufficient in most cities, and the cultivation of sustainable practices only happens with nature and the practicing of sustainable behaviors in daily life. Therefore, school gardens are emerging with a new approach that interprets these areas as learning landscapes, not just as spatial designs but as an approach that creates connections with the curriculum and ecology to help children learn about sustainability and builds bonds between nature and children in daily life.